THE PERCEPTION OF THE EFFECTIVENESS AND GOALS OF THE PREFERENTIAL CAR LOAN PROGRAM REINTRODUCED IN 2022 - Kanatbayev, Arkhat; Mussabekov, Aidar; Kunbulatova, Diana (Nazarbayev University, Graduate School of Public Policy, 2023)
The frequent instability of world commodity prices and recurrent crises have forced Kazakhstan to restructure its economy and move away from the extraction and export of raw materials. These occurrences prompted Kazakhstan to undertake an exploration of potential strategies that would optimize economic outcomes, therefore introducing preferential lending programs. Existing theories and concepts emphasize the significance of government incentives promoting the automotive industry for technological, economic, and industrial advancements. Study findings analyzed the efficacy and practices of various automotive industries in different countries. Our theoretical framework illustrates how preferential lending, influenced by international experiences and government policies, contributes to the development of the automotive sector in Kazakhstan. Paradoxically, limited research on the concentration of the car loan market and the effective implementation of preferential lending programs in Kazakhstan seems to exist. In this regard, employing a descriptive and comparative research approach through the utilization of surveys, collected from the public, stakeholders, and experts, enabled the gathering of relevant data regarding the respondents' perceptions of the goals and effectiveness of the preferential car loan program (hereinafter - the Program). Our survey revealed the need for a more precise definition of the Program's goals. The survey results showed that most of the respondents perceive the Program primarily as a tool to help citizens buy cars and support the domestic auto industry while others recognize it as harming the environment. Our project proposes recommendations to improve the efficiency and transparency of the Program. These include defining objectives, introducing digital solutions, enforcing financial controls, enhancing public awareness, preventing car price increases, incentivizing electric vehicle production, and taking a holistic approach to automotive industry development. Implementing these proposals will allow Kazakhstan to optimize the preferential car loan program and more effectively address its objectives.
Keywords: Automotive Sector Development; Preferential Lending; Government Policies; Economic Growth; Type of access: Open Access